Asymmetric polystyrene-polylactide bottlebrush random copolymers: Synthesis, self-assembly and nanoporous structures. (26th June 2019) - Cho, Seungwan; Son, Jinha; Kim, Inhye; Ahn, Hyungju; Jang, Hyun-Sook; Joo, Sang Hoon; Park, Kang Hyun; Lee, Eunji; Kim, Yongtae; Ahn, Suk-kyun
Abstract: Control of polymer architecture can be a powerful strategy to refine the structure and properties without changing the chemical structure of the monomers. Here, we exploit a highly branched bottlebrush architecture to access tailored self-assembled morphologies and nanoporous structures. To this end, a series of well-defined bottlebrush random copolymers are synthesized by macromonomer approach, where polystyrene (PS) and poly(D, L-lactide) (PLA) side chains of non-equal molecular weights are grafted to the polynorbornene backbone. These bottlebrush copolymers exhibit microphase-separated structures including lamellar, hexagonal cylinders and disordered structures with the domain sizes of 13–20 nm depending on the relative volume fraction ( f ) of PS and PLA side chain. Due to highly asymmetric nature, these bottlebrush copolymers exhibit cylinders at f PS = 41–50% and lamellar at f PS = 67–70%, unlike the case of linear diblock copolymers. The selective degradation of PLA from these bottlebrushes allows for nanoporous structures to be created of which size, distribution and connectivity of pores are dictated by the composition of bottlebrush precursors. The ability to exploit the bottlebrush architecture to manipulate self-assembled morphologies and nanoporous structures may be a useful way to design materials for adsorptions, separations, catalysis and gas storages. Graphical abstract: Image 1 Highlights: Asymmetric bottlebrush random copolymers comprising polystyrene (2.0 kDa) and poly(D, L-lactide) (PLA, 5.6 kDa) side chains are synthesized by grafting-through approach. Due to highly asymmetric nature, the bottlebrush copolymers exhibit cylindrical structure at f PS = 41–50% and lamellar structure at f PS = 67–70% unlike the case of linear diblock copolymers. The tunable nanoporous structures are obtained by selective degradation of PLA from the bottlebrush precursors.